2023
DOI: 10.55365/1923.x2023.21.37
|View full text |Cite
|
Sign up to set email alerts
|

China's Economic Stability Through Management of Rural Education Development: Condition and Possibilities

Abstract: As the largest developing country, China has made significant achievements in the battle against poverty in a short period. The key point lies in the targeted rural poverty alleviation policies with Chinese characteristics, for which educational poverty alleviation is the fundamental guarantee. Educational poverty alleviation in rural povertystricken areas is mainly to improve the total amount and quality of rural human resources with the adoption of various education-based human resource development models. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…"Internet plus" also provides rich learning resources for children, such as online courses and interactive games, which stimulates children's interest and enthusiasm in learning. Iryna et al (2023) studied the influence of online education on urban students and middle school students from rural low-income families. It is found that there is no statistically significant difference in knowledge acquisition between students from disadvantaged groups who have not received formal education and those who have received formal education after learning through MOOC(Massive open online course).…”
Section: Literature Reviewmentioning
confidence: 99%
“…"Internet plus" also provides rich learning resources for children, such as online courses and interactive games, which stimulates children's interest and enthusiasm in learning. Iryna et al (2023) studied the influence of online education on urban students and middle school students from rural low-income families. It is found that there is no statistically significant difference in knowledge acquisition between students from disadvantaged groups who have not received formal education and those who have received formal education after learning through MOOC(Massive open online course).…”
Section: Literature Reviewmentioning
confidence: 99%